Book Review - Gregor, Eugene C. (Columbia Journal of Environmental Law, 2020)
THE BAD EARTH: ENVIRONMENTAL DEGRADATION IN CHINA, by Vaclav Smil. Armonk, N.Y.: M.E. Sharpe, Inc.; London: Zed Press, 1984. Pp. xvi, 247. Cloth 25.00, Paper 13.95.*